(untitled) (Alberta Journal of Educational Research, 2014)
The arts have always had a profound impact on our lives: whether it be to express an idea, emotion, or as a way to communicate. Our worldly artistic experiences and knowledge date as far back as the Pre-historic period. So why is it that music, dance, drama, and visual arts, all cultural subjects so steeped in human history are, for the most part, always on the cutting block in educational curriculum? Why is artistic importance in the curriculum always viewed as mundane and devalued by so many policy makers? Following her best selling book Why Our Schools Need the Arts, author Jessica Hoffman Davis brings us Why Our High Schools Need the Arts. In arguing for an increase in arts courses within the educational curriculum as a way to engage all students and to alleviate the drop out rates of disenfranchised youth, Hoffman Davis offers vivid accounts from students, teachers, administrators “to provide the reader (the high school student, concerned parent, school administrator, teacher, arts education advocate, and/or policymaker) with the necessary information and perspective with which to argue for a prominent place for the arts in the reformation of high school curriculum” (p. 5).